2011
DOI: 10.4103/2229-5178.86007
|View full text |Cite
|
Sign up to set email alerts
|

Fumaric acid esters in dermatology

Abstract: Fumaric acid esters (FAE) are substances of interest in dermatology. FAE exert various activities on cutaneous cells and cytokine networks. So far only a mixture of dimethylfumarate (DMF) and three salts of monoethylfumarate (MEF) have gained approval for the oral treatment of moderate-to-severe plaque-type psoriasis in Germany. DMF seems to be the major active component. There is evidence that FAE are not only effective and safe in psoriasis but granulomatous non-infectious diseases like granuloma annulare, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…The main side effects associated with FAEs include gastrointestinal, flushing, reversible elevation of transaminases, lymphocytopenia, and eosinophilia. 125 Antimalarials are often used in the treatment of generalized GA. Chloroquine (250 mg daily) was successfully used in a patient with photodistributed GA. 126 Hydroxychloroquine has been used in the treatment of generalized GA. 127,128 Cannistraci and colleagues 127 treated 9 patients with generalized GA with 4 months of hydroxychloroquine (9 mg/kg/d for 2 months; 6 mg/kg/d for month 3; and 2 mg/kg/d for month 4). In this series of patients, complete remission was seen in all patients within 6 to 7 weeks of initiation of therapy.…”
Section: Evaluation and Managementmentioning
confidence: 99%
“…The main side effects associated with FAEs include gastrointestinal, flushing, reversible elevation of transaminases, lymphocytopenia, and eosinophilia. 125 Antimalarials are often used in the treatment of generalized GA. Chloroquine (250 mg daily) was successfully used in a patient with photodistributed GA. 126 Hydroxychloroquine has been used in the treatment of generalized GA. 127,128 Cannistraci and colleagues 127 treated 9 patients with generalized GA with 4 months of hydroxychloroquine (9 mg/kg/d for 2 months; 6 mg/kg/d for month 3; and 2 mg/kg/d for month 4). In this series of patients, complete remission was seen in all patients within 6 to 7 weeks of initiation of therapy.…”
Section: Evaluation and Managementmentioning
confidence: 99%
“…Treatment with FAEs has been reported to be effective not only in patients with sarcoidosis but also with other granulomatous diseases, such as disseminated granuloma annulare and necrobiosis lipoidica [5,6,7]. Recently, four cases with virus-related progressive multifocal encephalopathy (PML) were reported in patients with psoriasis under FAEs treatment [15].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond that, several reports have described an effect of FAEs on granulomatous skin diseases such as sarcoidosis, necrobiosis lipoidica and granuloma annulare [5,6,7]. However, very little is known about their mechanism(s) of action.…”
Section: Introductionmentioning
confidence: 99%
“…9 Other diseases, such as necrobiosis lipoidica, granuloma annulare, and sarcoidosis were also found in case reports or small patient series to respond to treatment with DMF. 28 Recently, Phase III clinical trials found that DMF (BG-12) successfully reduced the relapse rate and time to progression of disability in people with multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%